STRATEGI KOMUNIKASI PEMASARAN BATIK GONGGONG “LAWANA” TANJUNGPINANG DALAM MEMBANGUN BRAND AWARENESS - Ajura Nur; Muhammad Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The term of gonggong sounds foreign or strange impression for people outside the Kepulauan Riau. But for people in the Kepulauan Riau, is no stranger to this one sea slug. Gonggong (Strombus Turturella) is one of the many sea slug that are found around the Kepri waters. Batik Gonggong is new textile design in Indonesia. In 2010 open Selaras Shop as a manufacturer of batik gonggong with the brand "Lawana". In building brand awareness can be done through marketing communications. But in reality brand awareness is not present in the minds of consumers. Therefore, companies need to first know the marketing communication strategy that needs to be done for effective marketing.The type of research is qualitative with the presentation of descriptive analysis. The technique of collecting data through observation, interviews and documentation. Research subjects are Owner, Batik Designer, Employee and Constumer with purposive technique.The results of this study indicate that the segmentation of Batik Gonggong "Lawana" Tanjungpinang is from adults until children, Targeting, is for all circles, especially consumers who are interested in batik, and Positioning which has a unique style, limited edition motifs, and many options. Marketing communication strategy is done through advertising that is using electronic media and print media. Personal selling is done by direct presentation to consumers who come to the outlet, and also in events held by government agencies,private organizations and so on. Public Relations,opened mini workshop and build relationship with some government agencies. Direct marketing activities that use the phone and e-mail.Keywords: Gonggong, Brand Awareness, Marketing Communication